CHANGING BEHAVIOR AND MAKING IT IDENTITY; THE ORGANIZING OF COMMUNITY BEHAVIOR AROUND PESANTREN - Bilal, Bilal (Managere: Indonesian Journal of Educational Management, 2019)
Social and religious behavior is the act of carrying out religious teachings carried out with full confidence and sincerity and implemented in the social area of ​​society. In management, especially in the organizational dimension, there is integration between the individual's vision and the vision of the pesantren as the organizer, which is why the activities organized by the pesantren are able to run dynamically. The activities organized by the pesantren as non-formal educational institutions have a positive impact on the surrounding community, although not all activities have the same impact as what happens in the pesantren study activities. The results of this study indicate that; first, the change in community behavior after attending a routine study at the Istiqomah Islamic Boarding School in Pasuruan is through several stages, namely pre-contemplation, contemplation, preparation, action and maintenance. Second, the results achieved from routine activities at the Istiqomah Islamic boarding school are; a) increased faith and devotion, b) able to perform worship properly and consistently, especially prayer, c) have a good religious experience as evidenced by a feeling of calm when and after practicing worship, d) high interest in studying religious knowledge, e) more has good manners in interacting with neighbors or fellow Muslims, and f) living life in peace.